Optimization of the technology for obtaining ecdysterone from Serratula coronata L. by varying the extraction methods and growth phases - Temirgaziev, B.S.; Tuleuov, U.B.; Baizhigit, E.A.; Minayeva, Ye.V.; Salkeyeva, L.K.; Tuleuov, B.I.; Adekenov, S.M. (Ye.A.Buketov Karaganda State University Publishing house, 2018)
complex study of the aerial part of Serratula coronata L. cultivated in the collection area of medicinal plants of the IRPH «Phytochemistry» (Karaganda) in different phases of growth and using the most optimal extraction methods has been carried out. The content of the main active component of ecdysterone (20E)has been studied. Investigation of the seasonal dynamics of ecdysterone distribution under conditions of varying extraction methods shows that its maximum accumulation is observed during the vegetative phase, and the optimal method in this phase is extraction with isobutyl alcohol, the extract of which contains 13.86 % of ecdysterone and the maceration method with 96.2 % ethyl alcohol with a 20E content of 12.03 %, respectively. It is shown that the maceration with 96.2 % ethyl alcohol is technologically optimal, which fully complies with the international standards of good manufacturing practice (GMP) under pharmaceutical production conditions and excludes the use of toxic and expensive isobutyl alcohol solvent. It has been found that the content of ecdysterone from the beginning of vegetation to the final phase goes down, which is confirmed by the data of high-performance liquid chromatography (HPLC). It is assumed that there is an outflow of ecdysterone to the root system, and then its redistribution occurs as the plant develops further with a partial discharge into the soil. Based on the data on the quantitative content of the target component by the HPLC method, it is recommended that for the preparation of the ecdysterone substance of many actoprotective phytopreparations and valuable WS, the preparation of the above-ground biomass of Serratula coronata L. should be carried out during the vegetation phase of this taxon.
Экстракция əдістері мен өсу фазаларын түрлендіру арқылы тəжді түймебас өсімдігінен экдистерон алу технологиясын оңтайландыру
Оптимизация технологии получения экдистерона из серпухи венценосной варьированием методов экстракции и фаз произрастания
Keywords: Serratula coronata L.; aerial part; 20-hydroxyecdysone; high-performance liquid chromatography; extraction; ethyl alcohol; growth phase; vegetation